The Influence Of Digital Financial Literacy On Financial Well-Being With Financial Behavior As A Moderation Variable: Communities In West Sumatra - Aulia, Amalda; Rahayu, Rita; Bahari, Asniati (Jurnal Akuntansi, 2023)
This study aims to determine the relationship between digital financial literacy and financial well-being, and financial behavior moderates the relationship between the two. Digital financial literacy is a combined concept between financial literacy and digital aspects. Financial well-being is considered a benchmark or a person's level of satisfaction with his financial status, which can be seen from the amount and quantity. The data obtained were 215 respondents spread throughout the West Sumatra region. Data collection uses a questionnaire distributed via Google Forms on several social media applications. The approach in this study is quantitative, and the design of this study is hypothesis testing which aims to examine the effect of each variable. The study results show a significant influence between digital financial literacy and financial well-being, and financial behavior significantly moderates the relationship between digital financial literacy and the financial well-being of people in West Sumatra.